Neurometabolite Changes in Hyperthyroid Patients Before and After Antithyroid Treatment: An in vivo1H MRS Study - Kumar, Mukesh; Singh, Sadhana; Rana, Poonam; Kumar, Pawan; Sekhri, Tarun; Kanwar, Ratnesh; D’Souza, Maria; Khushu, Subash (Frontiers in Human Neuroscience, 2021)
Purpose: Patients with hyperthyroidism have frequent neuropsychiatric symptoms such as lack of attention, concentration, poor memory, impaired executive functions, depression, and anxiety. These neurocognitive impairments such as memory, attention, and executive functions appear to be associated with dysfunction in brain regions. This study was conducted to investigate the metabolic changes in the brain subcortical regions, i.e., posterior parietal cortex and dorsolateral prefrontal cortex (DLPFC), in patients with hyperthyroidism before and after antithyroid treatment using proton magnetic resonance spectroscopy (1H MRS). Materials and Methods: We collected neuropsychological and 1H MRS data from posterior parietal cortex and DLPFC, in both control (N = 30) and hyperthyroid (N = 30) patients. In addition, follow-up data were available for 19 patients treated with carbimazole for 30 weeks. The relative ratios of the neurometabolites were calculated using the Linear Combination Model (LCModel). Analysis of co-variance using Bonferroni correction was performed between healthy controls and hyperthyroid patients, and a paired t-test was applied in patients at baseline and follow-up. Spearman’s rank-order correlation was used to analyze bivariate associations between thyroid hormone levels and metabolite ratios, and the partial correlation analysis was performed between neuropsychological scores and metabolite ratios, with age and sex as covariates, in the patients before and after treatment. Results: Our results revealed a significant decrease in choline/creatine [glycerophosphocholine (GPC) + phosphocholine (PCh)/creatine (tCr)] in both the posterior parietal cortex and DLPFC in hyperthyroid patients, and these changes were reversible after antithyroid treatment. The posterior parietal cortex also showed significantly reduced glutamate/creatine (Glu/tCr), (glutamate + glutamine)/creatine (Glx/tCr), and increased glutathione/creatine (GSH/tCr) ratios in the hyperthyroid patients over control subjects. In DLPFC, only (N-acetyl aspartate + N-acetyl aspartyl-glutamate)/creatine (NAA + NAAG)/tCr was increased in the hyperthyroid patients. After antithyroid treatment, (GPC + PCh)/tCr increased, and Glx/tCr decreased in both brain regions in the patients at follow-up. Gln/tCr in the posterior parietal cortex was decreased in patients at follow-up. Interestingly, (GPC + PCh)/tCr in DLPFC showed a significantly inverse correlation with free tri-iodothyronine (fT3) in hyperthyroid patients at baseline, whereas NAA/tCr showed positive correlations with fT3 and free thyroxine (fT4) in hyperthyroid patients before and after antithyroid treatment, in the posterior parietal cortex. In DLPFC, only (NAA + NAAG)/tCr showed positive correlations with fT3 and fT4 in the patients before treatment. Conclusion: The overall findings suggest that all the brain metabolite changes were not completely reversed in the hyperthyroid patients after antithyroid treatment, even after achieving euthyroidism.